Pengaruh Celebrity Endorsement Pada Media Sosial Instagram Terhadap Purchase Intention Pada ProdukPakaian Olahraga Adidas dengan Brand Image Sebagai Varibel Mediasi - Widiarsana, Nyoman Andika Bryan Prabawa (Jurnal Ilmiah Mahasiswa FEB, 2017)
The development of the sports world has entered the realm of industry, where famous brands compete in marketing their products such as sportswear and sports equipment. It makes the famous brands compete in marketing their products, One of them by using social media Instagram and use celebrity endorsement.This research is aimed at determining and analyzing the direct and indirect  celebrity endorsement on purchase intention on Adidas sportswear mediated by brand image as the  intervening  variable.  This explanatory research explains the causal relationship between variables through hypothesis testingThrough non-probability sampling carried out on students in Malang who never bought any Adidas sportwear product, this research has selected 100 respondents as the sample. The hypothesis testing is done using t test and Sobel test. The data are analyzed using Partial Least Squares (PLS), supported by Smart PLS 3.0. Based on the four hypotheses, it can be concluded that the variable of celebrity endorsement has a positive and significant effect on the variable of brand image of Adidas Sportwear The  variable  of  celebrity endorsement  has  a  positive  and significant  effect  on purchase  intention  Adidas sportswear. The variable of brand image has a positive and significant effect on customer’s intention to purchase Adidas sportswear. The variable of celebrity endorsement has a positive and significant impact on consumer’s intention to purchase Adidas sportwear mediated by brand imageKEYWORDS: Celebrity Endorsement, Brand  Image,  Purchase Intention